Complementary and alternative medicine (CAM) practices and dietary patterns in children with inflammatory bowel disease in Singapore and Malaysia - Ong, Fangyi; Lee, Way Seah; Lin, Charlotte; Ng, Ruey Terng; Wong, Shin Yee; Lim, Su Lin; Quak, Seng Hock; Aw, Marion Margaret (Elsevier, 2018)
Background: The use of complementary and alternative medicine (CAM) has been associated with adverse effects and self-imposed dietary restrictions. The prevalence of its use in Asian children with inflammatory bowel disease (IBD) is unknown. We aimed to determine the prevalence, types, and factors associated with the use of CAM among children with IBD from Singapore and Malaysia, and to ascertain if dietary restriction was prevalent in patients who used CAM. Methods: A cross-sectional study was conducted in which parents of children with IBD attending two tertiary pediatric IBD referral centres in Singapore and Malaysia were interviewed. Data about demographics, conventional treatment, complementary therapies and dietary patterns were collected in a questionnaire. Results: Of 64 children with IBD interviewed, 83% (n = 53) reported the use of CAM (Singapore [90%] vs. Malaysia [76%]; p = 0.152). The median number of CAM agents used was two (range 1–10). The three most common types of CAM used were probiotics (64%), vitamin and mineral supplements (55%), and food-based therapies (36%). Among individual CAM categories, the use of food-based therapies was correlated significantly with nationality (r = 0.497, p < 0.001), history of weight loss due to IBD (r = 0.340, p = 0.013) and avoidance of certain foods to prevent a relapse (r = 0.289, p = 0.036). Parents who rated their child's disease activity as more severe were less likely to use CAM (r = −0.257, p = 0.041). Fifty-nine percent of CAM users reported physician awareness of their CAM use. The overall self-perceived efficacy of CAM in improving IBD symptoms was 34%. Of the dietary patterns explored, only intake of dairy products was associated with CAM use (r = 0.306, p = 0.019). Conclusion: Use of CAM is prevalent in children with IBD in Malaysia and Singapore. Further studies to elucidate reasons influencing CAM use, dietary patterns and efficacy of commonly used CAM would be required.